2017
DOI: 10.5897/ajb2017.15888
|View full text |Cite
|
Sign up to set email alerts
|

Anaerobic and micro-aerobic 1,3-propanediol production by engineered Escherichia coli with dha genes from Klebsiella pneumoniae GLC29

Abstract: 1,3-Propanediol (1,3-PDO) is a bifunctional molecule, and used in applications similar to those of ethylene glycol, propylene glycol, 1,3-butanediol and 1,4-butanediol. The use of glycerol as a feedstock is an alternative to reduce production costs for both 1,3-PDO and biodiesel, since biodiesel glycerol can be used for the production of 1,3-PDO by bacteria. Also, using metabolic engineering, it is possible to manipulate the metabolic routes and obtain high value products, reduce or eliminate the formation of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
5
1

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(6 citation statements)
references
References 22 publications
0
5
1
Order By: Relevance
“…3(F)). Our results were different from several previous reports in which anaerobic and microaerobic conditions were previously recommended as suitable conditions to produce 1,3‐PDO by either K. pneumoniae or Lactobacillus reuteri 8,17,18 . Those works assumed that GDht effectively functioned under anaerobic conditions 19 .…”
Section: Resultscontrasting
confidence: 99%
See 4 more Smart Citations
“…3(F)). Our results were different from several previous reports in which anaerobic and microaerobic conditions were previously recommended as suitable conditions to produce 1,3‐PDO by either K. pneumoniae or Lactobacillus reuteri 8,17,18 . Those works assumed that GDht effectively functioned under anaerobic conditions 19 .…”
Section: Resultscontrasting
confidence: 99%
“…2(B)), while glycerol consumption and 1,3‐PDO production were stalled after 102 h. The results suggested that adenosyl transferase activity of E. coli may not be efficient enough to generate the adenosylated vitamin B12 to maximum level for supporting the full activity of GDHt compared to those directly utilizing coenzyme B12. Compared to other works, Neto et al 17 . used 0.25 mg L −1 (0.18 μmol L −1 ) vitamin B12 to produce 2.5 g L −1 1,3‐PDO (0.41 g g −1 yield) in batch fermentation, while Zhang et al 9 .…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations